Stimulated Bile Production and Outflow in the Prevention and Treatment of Acute Hepatic Failure - R. V. Bukhov (Общая реаниматология, 2006)
Objective. To employ bile stimulation as a method for preventing and treating acute hepatic failure.Materials and methods. The results of the clinical examination and treatment of 52 inpatients treated for obstructive jaundice-complicated cholelithiasis, by stimulating bile production and outflow.Results. All the patients with acute hepatic failure underwent 48 endoscopic interventions (endoscopic papillosphincterotomy) and 4 choledochotomy, followed by stimulation of bile production and outflow. Enhanced bile production and outflow with adequate bile outflow into the duodenum completely evacuated gallstones from the biliary tract into the duodenum and normalized the composition of hepatic bile, which could, as a rule, get clear of the signs of hepatic failure completely within 10—12 days.Conclusion. The actual possibility exists of treating and preventing acute hepatic failure, by stimulating bile production and outflow in patients with obstructive jaundice-complicated cholelithiasis. Open-access surgery (laparotomy, choledochotomy, external choledochal drainage) is indicated when endoscopic drainage of the bilious tree is ineffective and when the clinical manifestations of hepatic failure increase in cholelithiasis.